Past and present of allspice (Pimenta dioica) in Mexico and Guatemala - Paulina Machuca; María Teresa Pulido-Salas; Felipe Trabanino (Revue d'ethnoécologie)
European expansion in the 16th Century produced a worldwide circulation of plants.Spanish colonialism displaced native plant resources while also promoting a mixture of Old and New World food cultures. That is the case of allspice, the fruit of the Pimenta dioica (L.) Merrill, a native tree to tropical forest in Mesoamerica that eventually became highly valued as a spice in global markets. For this study we trace the trade history of allspice and describe some common current traditional practices for harvest and commercial production strategies. Initially confused with other pepper-like spices, allspice was partially marginalized during the first two centuries of Spanish colonization, but later support from the Spanish Crown helped it to become actively traded beginning in the 18th Century. In Guatemala, its region of natural distribution, allspice is still produced following traditional techniques and is commercialized in local markets, although there are well-established large-scale producers in Mexico that export it. The present study aims at integrating experiences over time and under various conditions, from history and present days, to provide a better understanding of the elements that contributed to the resurgence of allspice from being a marginalized crop to one prized worldwide. We conclude that allspice survived the vicissitudes of colonialization partially due to government intervention, and eventually became a valuable commodity, even in our days.